Posttraumatic growth of medical staff during COVID-19 pandemic: A scoping review - Qian Li; Yirong Zhu; Xuefeng Qi; Haifei Lu; Nafei Han; Yan Xiang; Jingjing Guo; Lizhu Wang (BMC, 2024)
Abstract Background The COVID-19 pandemic has imposed unprecedented stress and challenges upon medical staff, potentially resulting in posttraumatic growth (PTG). This scoping review aims to synthesize the existing knowledge on PTG among medical staff during the pandemic by identifying its current status and potential influencing factors. The findings may provide a foundation for future research and interventions to enhance the medical staff's psychological resilience and well-being. Methods Literature was systematically searched on PTG among medical staff during the COVID-19 pandemic from 01 January 2020 to 31 December 2022. The following databases were searched: PubMed, Web of Science, Embase, CINAHL, PsycINFO, Cochrane Library, China National Knowledge Infrastructure (CNKI), Chinese Biomedical Literature Service System (SinoMed), and Wanfang Data. Eligibility criteria included: (1) medical staff as research subjects; (2) a focus on "posttraumatic growth" or "alternative posttraumatic growth" related to the COVID-19 outbreak and pandemic; (3) discussion of the situation and influencing factors of PTG; and (4) study types, such as qualitative, quantitative, and mixed methods. Two researchers independently selected and extracted study characteristics (study design, study population, region, measurement instruments, and primary outcomes) from the included literature. The data were synthesized qualitatively and descriptively. Results Thirty-six papers from 12 countries met the inclusion criteria. Moderate PTG levels were observed among healthcare workers during the COVID-19 pandemic, with emphasis on "interpersonal relationships," "changes in life philosophy," and "growth in personal competence." Influencing factors included trauma exposure, sociodemographics, psychological characteristics (resilience and positive qualities), coping, and social support. Conclusions This review discovered moderate PTG levels among medical staff during the COVID-19 pandemic, with critical areas in interpersonal relationships, life philosophy, and personal competence. The identified influencing factors can inform future research and interventions to enhance healthcare workers' psychological resilience and well-being.